Biological control of plant diseases (The Journal of Plant Protection Sciences, 2021)
Biological control of plant diseases seems to be the best alternative for plant disease control. It is ecofriendly, reliable, cost  effective and is an integral component of integrated plant disease management framework for sustainable crop  production. A considerable number of biocontrol agents have been established successfully for their bioconrol potential  including strains belonging to bacterial genera such as Agrobacterium, Pseudomonas, Streptomyces and Bacillus, and  fungal genera such as Gliocladium, Trichoderma, Ampelomyces, Candida and Coniothyrium. Trichoderma and  Pseudomonas fluorescens are the most important and widely used bioconrol agents being used across the world for the  management of several plant diseases. Some bacterial biocontrol agents can inhibit both bacterial and fungal pathogens.  Smilarly, fungal-fungal, fungal-bacteria and actinomycete-fungal/actinomycete interactions exist in nature and opens a  new area of research in biocontrol of plant diseases. The mechanisms of action of these biocontrol agents against target  pathogens are antibiosis, mycoparasitism, competition for space and nutrient, production of certain toxins and secondary  metabolites, solublization and sequestration of immobilized plant nutrients, plant growth prowth promoting properties  and induced resistance. Multiple interactions between bacteria-fungi-actinomycete, may exist in nature and that is why  consortium of microorganisms is needed for tackling several plant pathogens simultaneously instead of only one  biocontrol agent-one pathogen,which is the most common and established system of biocontrol of plant diseases.
Keywords: Biocontrol agents; bacteria; fungi; actinomycete; plant diseases